DETERMINANTS OF CUSTOMER COMMITMENT OF SHARIA BANKS PALOPO BRANCH OFFICE - Ishak; Madinah Syarah; Mujahidin (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the influence of murabahah financing, Islamic service ethics, and service accessibility on customer commitment at Bank Syariah Indonesia (BSI) Palopo Branch Office. This study was conducted as an effort to fill the gap in previous research which generally focused more on the aspects of customer satisfaction and loyalty, while customer commitment as a form of long-term relationship is still relatively rarely studied in depth. This study uses a quantitative approach with a survey method. The population in this study is all active customers of BSI Palopo Branch Office which is 23,818 customers. The sample was determined using the Slovin formula so that as many as 100 respondents were obtained by purposive sampling technique. Data were collected through a structured questionnaire, then analyzed using multiple linear regression, classical assumption test, t test, F test, and determination coefficient with the help of SPSS software. The results of the study show that partially murabahah financing has a positive and significant influence on customer commitment. Meanwhile, Islamic service ethics and service accessibility did not have a significant impact, although both showed a positive relationship direction. Simultaneously, these three variables have been proven to have a significant effect on customer commitment. The value of the determination coefficient shows that the research model is able to explain some of the variations in customer commitment. This study has limitations because it was only conducted at one research site with a relatively limited number of respondents, so generalization of results needs to be done carefully. Therefore, further research is recommended to expand the coverage of the region and add other variables in order to obtain more comprehensive results. This research makes a new contribution by integrating murabahah financing, Islamic service ethics, and service accessibility in explaining customer commitment in the context of Islamic banking at the local level.